Proximal clustering between BK and CaV1.3 channels promotes functional coupling and BK channel activation at low voltage - Vivas, Oscar; Moreno, Claudia M; Santana, Luis F; Hille, Bertil (eLife, 2017)
CaV-channel dependent activation of BK channels is critical for feedback control of both calcium influx and cell excitability. Here we addressed the functional and spatial interaction between BK and CaV1.3 channels, unique CaV1 channels that activate at low voltages. We found that when BK and CaV1.3 channels were co-expressed in the same cell, BK channels started activating near −50 mV, ~30 mV more negative than for activation of co-expressed BK and high-voltage activated CaV2.2 channels. In addition, single-molecule localization microscopy revealed striking clusters of CaV1.3 channels surrounding clusters of BK channels and forming a multi-channel complex both in a heterologous system and in rat hippocampal and sympathetic neurons. We propose that this spatial arrangement allows tight tracking between local BK channel activation and the gating of CaV1.3 channels at quite negative membrane potentials, facilitating the regulation of neuronal excitability at voltages close to the threshold to fire action potentials.